Optimasi Dosis Radiasi pada Pemeriksaan CT-Scan Brain dengan Klinis Stroke Non Hemoragik di Rumah Sakit Otak DR. DRS. M. Hatta Bukittinggi - Zasneda, Sabriani Suci; Kustoyo, Bambang; Hulu, Yessi Vanni; Saragih, Febby Lolasari (Prosiding Seminar Kesehatan Nasional, 2023)
Stroke non-hemorrhagic requires rapid and accurate diagnostic imaging using CT-Scan examination. However, CT-Scan is associated with relatively high radiation exposure. This study aims to evaluate radiation dose in CT-Scan brain examination with non-hemorrhagic stroke clinical indication and identify optimization strategies based on ALARA principles. This descriptive research with quantitative approach was conducted at Radiology Installation of RS Otak DR. Drs. M. HATTA Bukittinggi from June to August 2023. Data were collected from 50 CT-Scan brain examinations with stroke clinical indication, including CTDIvol, DLP, and effective dose measurements. Technical parameters analyzed include kVp, mAs, slice thickness, and scan length. Results showed mean CTDIvol of 52.3±8.7 mGy, mean DLP of 1024.5±156.2 mGy.cm, and mean effective dose of 2.05±0.31 mSv. These values are within acceptable diagnostic reference levels (DRL) but can still be optimized. Factors affecting radiation dose include patient body habitus (r=0.68, p<0.001), scan length (r=0.72, p<0.001), and tube current selection (r=0.81, p<0.001). Optimization strategies identified include implementation of automatic tube current modulation (ATCM), scan length limitation to necessary areas only, and use of iterative reconstruction techniques. Implementation of these optimization strategies can reduce radiation dose by 30-40% without compromising diagnostic image quality. Conclusion: Radiation dose in CT-Scan brain examination for stroke cases at RS Otak DR. Drs. M. HATTA Bukittinggi is within acceptable limits but requires continuous optimization through implementation of dose reduction techniques while maintaining diagnostic quality according to ALARA principles